2005
DOI: 10.1007/s10720-005-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of CuCr2Se4 ferromagnetic spinel microcrystals in a chalcogenide glass matrix

Abstract: Crystals of the CuCr 2 Se 4 ferromagnetic spinel and spinel-based solid solutions are shown to form in glass-forming alloys of the Cu 2 Se-As 2 Se 3 -Cr 2 Se 3 -Se system containing Cr 2 Se 3 at a content greater than 0.005 mole fractions. The crystalline phases are identified by the magnetochemical method (from the Curie temperatures) and X-ray diffraction analysis. According to electron microscopy, the crystal sizes are equal to several micrometers. IR irradiation of the samples in a magnetic field leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The choice of the radiation wavelength was motivated by the following circumstances. One of the methods for preparing finely dispersed CuCr 2 Se 4 spinel crystals consists in forming this spinel in a matrix of glasses in the Cu 2 Se-As 2 Se 3 system [21].…”
Section: Sample Preparation and Experimental Techniquementioning
confidence: 99%
“…The choice of the radiation wavelength was motivated by the following circumstances. One of the methods for preparing finely dispersed CuCr 2 Se 4 spinel crystals consists in forming this spinel in a matrix of glasses in the Cu 2 Se-As 2 Se 3 system [21].…”
Section: Sample Preparation and Experimental Techniquementioning
confidence: 99%
“…First, Tver'yanovich et al demonstrated in 2005 the possibility to generate CuCr 2 Se 4 ferromagnetic spinel microcrystals in a Cu 2 Se-as 2 Se 3 -Cr 2 Se 3 glassy system (Tver'yanovich et al, 2005). While no information is given on the infrared transparency of the glass-ceramics, it is interesting to note that when samples are placed in a magnetic field and irradiated by an IR source, an increase of the magnetization is observed.…”
Section: Other Ir Transparent Glass-ceramicsmentioning
confidence: 99%